(3GdbVGA hGdTgGOGJs - (3GdRQjbj, GdfLaj, GdRQjLGhj, eMeO Hf WYeI GdRQjbj GdfLaj, GdeYQha HGdTjN eMeO GdRQjLGhjs ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdbVGA HGdeO hbO jbUQ hgh dZI deYGf YOjOI dcf jecf GQLGY HYVgG Edi HYV efgG aYd GdTjA hGdGJjGf Hgs
(3BNQgG (B:s
(3BNQgG(B: (3hGdOYhi GdefaQOI (B.. (3dG eYGQV dgG HCf jOYj fSH eLghd GdfSH hdG jfGRYg ajg CMO heYfi GTJQGcg Cf (B.. (3aUGYOG hcPG GdOYhi GdeTJQcI jdMbhfgG HGdfSH hjbVj ajg (B... (3ceG YQaJs
(3JHUQI GdeDda (B:s
(3cPG PcQg UGMH GdPQjYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B17: 93s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis